1998
DOI: 10.1080/0141192980240304
|View full text |Cite
|
Sign up to set email alerts
|

The Tutoring Process and its Manifestation in the Classroom Behaviour of Tutors and Tutees

Abstract: Three case studies were conducted of seventh graders teaching mathematics to third graders, in place of their classroom teacher, applying the Learning Through Teaching (LTT) method. Audio and video recording provided information on tutoring sessions. Trained observers coded the behaviours of the tutors and tutees during the tutoring sessions and in their respective classes during mathematics and other lessons. The results show that when tutors are appropriately prepared to teach their younger counterparts, sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…However, researchers in psychology and education [e.g., 2,3,8] have investigated the learning that takes place with tutors as well as tutees during peer tutoring experiences. (See Bar-Eli and Bar-Eli [1] for a more comprehensive review. )…”
Section: Literature Re Viewmentioning
confidence: 96%
See 1 more Smart Citation
“…However, researchers in psychology and education [e.g., 2,3,8] have investigated the learning that takes place with tutors as well as tutees during peer tutoring experiences. (See Bar-Eli and Bar-Eli [1] for a more comprehensive review. )…”
Section: Literature Re Viewmentioning
confidence: 96%
“…One example was a city-wide scavenger hunt called "The Challenge" , in which MYO students solved, among other things, mathematical conundrums. Another was a workshop entitled " Why Sma rt People Fail", addressing such issues as: (1) labeling and positive self-identity; (2) the forces for self destruction; (3) accomplishing one's goals; and (4) conflict resolut ion.…”
Section: Mental Toughnessmentioning
confidence: 99%
“…That interactions between tutor and tutee are important to the success of cross-age programs should be no surprise, however, relevant data examining the exact nature of effects of naturally occurring interactions in tuition programs is scarce. As recent researchers (e.g., Bar-Eli et al, 1998;Nugent, 2001) have suggested, further research needs to be done which can shed more light on the type of information and support that passes between tutor and tutee so that a better understanding of the learning effects found in cross-age tutoring can be achieved.…”
Section: Cross-aae Tutoringmentioning
confidence: 97%
“…Learning through teaching is a common learning approach which gives credits to tutor's benefits from peer tutoring. Increased content knowledge, advanced communicating and metacognitive skills, and amplified motivation are some of the tutors' benefits found in literature (Bar-Eli et al, 1998). Along the same lines, the study of Wright and Cleary (2006) revealed that tutors increased their reading rates and speed as a result of their participation in peer tutoring.…”
Section: Students' Academic Benefitsmentioning
confidence: 80%
“…As a result, children with SEND proved that they can implement effectively the role of tutors of children reading at a lower grade or younger than them. As a conclusion, children with SEND in the role of tutor has been found to improve not only their reading rates, but also their self-worth (Bar-Eli, Bar-Eli, Tenenbaum, & Forlin, 1998), by taking the role of helper, when they usually are the ones helped (King-Sears & Cummings, 1996).…”
Section: Students' Rolesmentioning
confidence: 85%